Community Assembly and Stability in the Root Microbiota During Early Plant Development - Aleklett, Kristin; Rosa, Daniel; Pickles, Brian John; Hart, Miranda M. (Frontiers in Microbiology, 2022)
Little is known about how community composition in the plant microbiome is affected by events throughout the life of the plant. For example, the timing root exposure to exogenous microbial communities could create variation in microbial community structure between mature plant root systems. We conducted two experiments explored if the composition of the root microbiota in mature plants could be determined by either the timing of root exposure to microbial communities or priority effects by early colonizing microbes. Timing of microbial exposure was manipulated through an inoculation experiment where plants of different ages, that had never been in contact with soil, were exposed to a common soil inoculum and then grown to maturity. Priority effects were manipulated by challenging roots with established microbiota with an exogenous microbial community. Results showed that even plants with existing microbial root communities, inoculated at a later stage, were able to acquire new microbial associates, but that timing of soil exposure did have a significant effect on composition of both bacterial and fungal communities in mature plants. Plants already colonized were only receptive to colonizers at one week post germination. Our study shows that timing of soil exposure in the early life stages of a plant is important for development of the root microbiota in mature plants.